Jugatala angulata - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Jugatala angulata (C.L. Koch, 1839) * Material – New record for Turkey. One specimen in Karadedeoğlu Village, Tekkeyaylasi forest area, Taşköprü-Kastamonu, N 41° 22′ 23.26′′, E 34° 24′ 22.11′′, alt. = 1187 m, 17 July 2018, tree bark of P. nigra . Global distribution – Europe. Ecology – Arboricolar, mostly on coniferous trees (spruce and pine). Remarks – Measurements: Body size: 600 × 370 µm. All characters match the description provided by Weigmann (2006), however, Bayartogtokh and Schatz (2008) report a smaller size (486 µm) for individuals found in Austria. Up to now J. angulata was known from Europe only (Weigmann 2006; Bayartogtokh and Schatz 2008). Our record broadens the area of occurrence for this species. We confirm habitat preference of J. angulata by finding it on the bark of the pine tree as originally described, however, Sobek et al. (2008) indicate presence of the species on broadleaved trees (beech and oak) as well.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 268, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Jugatala; Arthropoda; Arachnida; Ceratozetidae; Animalia; Biodiversity; Sarcoptiformes; Jugatala angulata; Taxonomy; 15. Life on land